(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2018)
The objective of the present work is to conduct analysis of solar collectors’ operation. The study includes development of a 3-D mathematical model of the collectors’ system and extensive numerical simulation, based on the computational fluid dynamics (CFD) approach. The main aim is forming a mathematical model that reflects the operation of the flat solar collector under changing conditions to determine the speed of flow of the working fluid, temperature distribution and the parameters that characterize the intensity of heat transfer, within any cross section at any given time. The analysis shows that the presented modelling approach can be used for further investigations.